Unique roles of childhood poverty and adversity in the development of lifetime co-occurring disorder - Jenna van Draanen (Elsevier, 2020)
Gender differences in stressors that affect the development of co-occurring psychiatric and substance use disorders (COD) have been given inadequate attention, despite evidence that women and men commonly develop different types of both psychiatric disorder and substance use disorders and have different experiences of illness and treatment. This paper assesses early life antecedents of COD, specifically childhood poverty and childhood adversity, and how they vary by gender. Weighted multinomial logistic regressions were conducted with the National Epidemiologic Survey of Alcohol and Related Conditions-III (NESARC-III) (n = 33,676) nationally representative data from 2014-2015 to assess whether antecedents of COD are conditional on gender. Results demonstrate that overall nearly one in five people (17.5%) have lifetime COD, and disorder prevalence differs for males and females (COD: 18.0% vs 16.4%; psychiatric disorder: 8.5% vs. 20.9%; substance use disorder: 5.6% vs. 13.0%, respectively). Males with childhood poverty are more likely than males without to have COD but poverty does not affect COD risk for females. For both males and females, increases in number of adversities are associated with increased probability of COD, however, the magnitude of this association is stronger for males. To understand COD risk, conditional relationships between early poverty, early adversity and gender must be considered. With this knowledge, prevention and treatment efforts have the potential to be targeted more effectively.